Tightly Secure Encryption Schemes against Related-Key Attacks. (7th August 2018) - Han, Shuai; Liu, Shengli; Lyu, Lin; Gu, Dawu
Abstract: ℱ -Related-Key Attacks (RKAs) allow an adversary to tamper the key k stored in a cryptographic device by specifying related-key deriving (RKD) functions f in ℱ and subsequently learn the outcome of the device under related keys f ( k ) . In this paper, we present RKA secure public-key encryption (PKE) and symmetric encryption (SE) schemes admitting a tight security reduction to the standard s -Linear assumption. The security loss depends only on the security parameter and is independent of the number of tampering queries made by the adversary. Our encryption schemes are resilient to RKAs w.r.t. the set of restricted affine functions ℱ raff, of which the set of linear functions ℱ lin is a subset. In particular, Our encryption schemes serve as the first ones possessing tight RKA security for a non-trivial RKD function class ℱ under standard assumptions. Moreover, our encryption schemes enjoy tight super-strong RKA securities, which are the strongest ones among the existing RKA security notions.